Structured handoff to improve communication from inpatient to outpatient dialysis units: A quality improvement project. Issue 2 (25th January 2023) - Claudel, Sophie E.; Valente, Christopher; Serafin, Hope; Hassan Kamel, Mohamed; Ghai, Sandeep
Abstract: Background: Patients with end‐stage kidney disease requiring dialysis encounter high hospital readmission rates. One contributor is poor communication between hospitals and outpatient dialysis facilities. We hypothesized that improved communication may reduce 30‐day hospital readmissions for patients on dialysis at an urban, safety net hospital. Methods: We created a standardized discharge handoff tool that is easy to use and provides concise data for dialysis centers. The handoff tool is a novel, electronic MACRO template (called a "dot‐phrase") to be included in discharge documentation. Instructions for the dot‐phrase and electronic facsimile (e‐faxing) were sent to Internal Medicine residents immediately prior to their rotation on an inpatient Renal service. We then measured the intervention implementation rate and its impact on hospital readmission metrics. Results: We compared 3 months of preintervention and 6 months of postintervention data, identifying 82 and 135 index discharges in each respective study period. Patients were predominantly male (56.2%) and receiving hemodialysis (89.8%); a minority (9.2%) were undomiciled at the time of discharge. Mean age was 60.5 years (SD 14.0). Renal discharges followed by 30‐day Renal readmission were not statistically lower in the postintervention group for the index discharge alone (26.8% vs. 20.0%, p = 0.12), but were for overall discharges (51.2% vs. 25.7%, p < 0.0001). The dot‐phrase was used in 95.4% of discharge summaries, and 74.7% of discharge summaries were e‐faxed within 24 h of discharge. Conclusion: There was high uptake of a standardized discharge handoff tool among Internal Medicine residents on a Renal inpatient service. Using a handoff tool and e‐faxing may improve communication with outpatient dialysis centers and may reduce readmissions among some patients but is likely insufficient to fully address high readmission rates. Subsequent intervention iterations would benefit from further collaboration with outpatient dialysis units for customization of the handoff tool to meet local communication needs.